2016
DOI: 10.21010/ajtcam.v13i4.17
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Herbs Used by Hiv-Positive People in Lesotho

Abstract: Background: The use of medicinal herbs whose efficacy and toxicities are not known by HIV-positive people in Lesotho is a threat to the effectiveness of antiretroviral treatment. This study explored some medicinal herbs used by HIV-positive people in Lesotho and the reasons for their use. Methods: This was a cross sectional study based on a questionnaire distributed to purposively-sampled HIV-positive people in Leribe and Maseru districts of Lesotho. The participants' socio-demographic and clinical variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…Our fnding on the herbal medicine use among PLWHA is comparable with reports from other African countries that reported a prevalence between 53.7% and 58% [11,14,34]. However, it is lower than the fndings reported by Haile et al [10] in northwest Ethiopia (70.8%) and another study in Lesotho (69.9%) [35] but higher than the prevalence of herbal medicine use reports by two studies in Uganda [15,36]. Te fndings between studies might be due to diferences in study populations, unstandardized defnitions for herbal medicine, and inclusion/exclusion criteria for specifc types of therapies in these studies.…”
Section: Discussionsupporting
confidence: 85%
“…Our fnding on the herbal medicine use among PLWHA is comparable with reports from other African countries that reported a prevalence between 53.7% and 58% [11,14,34]. However, it is lower than the fndings reported by Haile et al [10] in northwest Ethiopia (70.8%) and another study in Lesotho (69.9%) [35] but higher than the prevalence of herbal medicine use reports by two studies in Uganda [15,36]. Te fndings between studies might be due to diferences in study populations, unstandardized defnitions for herbal medicine, and inclusion/exclusion criteria for specifc types of therapies in these studies.…”
Section: Discussionsupporting
confidence: 85%
“…Conservation studies are essential since they provide critical information on the extent of the threat facing biodiversity to avoid over-exploitation and possible extinction of biological resources. This is particularly important because medicinal plants are heavily harvested in Lesotho to supply local and international markets (Motjotji 2011, Mojakhomo 2012, Masupha et al 2013, Mugomeri et al 2016b) This is also evidenced by several 'muthi' stalls in the informal markets of major towns such as Maseru and Maputsoe (Mojakhomo 2012, Masupha et al 2013, Mugomeri et al 2016b). In fact, (Masupha et al 2013) reported that more than 86% of traditional practitioners in Lesotho admitted to experiencing declining sources of plants and animals used in the preparation of traditional medicines.…”
Section: Conservation Studiesmentioning
confidence: 99%
“…The compounds exhibited activities with MIC values ranging from 0.1 mg/mL to 0.6 mg/mL, whereas combination of the two compounds exhibited activities with MIC values ranging from 0.2 mg/mL to 4.0 mg/mL; synergistic interactions were noted against E. coli and E. faecalis with ΣFIC values of 0.1 and 0.50, respectively [6]. Mugomeri et al [63] used the checkerboard microdilution technique to determine the efficacy of mixing (-)-epicatechin and palmitic acid or any of these two compounds with P. prunelloides against B. cereus, S. aureus, E. coli, K. pneumonia, and E. faecalis. The results demonstrated that the combinations resulted in either additive or synergistic effects, but no antagonistic interactions were observed [65].…”
Section: Antibacterial Activitiesmentioning
confidence: 99%